Comparison of Futsal Learning Through the Approach of Playing Using Plastic Ball Tools and Standard Balls to Passing Ability at SMAN 1 Cicalengka - Sani Tyas (STKIP Pasundan Press, 2026)
This study aims to determine the differences in futsal learning outcomes through a play approach using plastic balls and standard balls on students' passing abilities at SMAN 1 Cicalengka. The research method used was an experimental method with a pretest-posttest control group design. The population of this study consisted of all futsal extracurricular students at SMAN 1 Cicalengka. The sample was selected using simple random sampling, consisting of 30 students divided into two groups: the first group used plastic balls, and the second group used standard balls. Passing ability tests were conducted before and after the treatment. The data were analyzed using a t-test to determine the difference in passing improvement between the groups. The results showed a significant difference between the two groups. The group using standard balls showed a higher improvement in passing ability compared to the group using plastic balls. Therefore, the use of standard balls is more effective in improving students' passing ability through the play approach.